2020
DOI: 10.1186/s13578-020-00411-5
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone receptor beta is critical for intestinal remodeling during Xenopus tropicalis metamorphosis

Abstract: Background: Thyroid hormone (T3) is critical for development in all vertebrates. The mechanism underlying T3 effect has been difficult to study due to the uterus-enclosed nature of mammalian embryos. Anuran metamorphosis, which is dependent on T3 but independent of maternal influence, is an excellent model to study the roles of T3 and its receptors (TRs) during vertebrate development. We and others have reported various effects of TR knockout (TRα and TRβ) during Xenopus tropicalis development. However, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…ChIP-Seq identification of candidate TR target genes during intestinal remodeling. We and others have recently shown that knocking out of either TRα or TRβ delays intestinal remodeling during natural and/or T3 induced metamorphosis 11,[13][14][15]18 . RNA-Seq analysis of the intestine of premetamorphic wild-type and TRα −/− tadpoles treated with or without T3 for 18 h revealed that most of the T3 regulated genes were dependent on TRα, suggesting that TRα plays a dominant role early during T3induced intestinal remodeling 19 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…ChIP-Seq identification of candidate TR target genes during intestinal remodeling. We and others have recently shown that knocking out of either TRα or TRβ delays intestinal remodeling during natural and/or T3 induced metamorphosis 11,[13][14][15]18 . RNA-Seq analysis of the intestine of premetamorphic wild-type and TRα −/− tadpoles treated with or without T3 for 18 h revealed that most of the T3 regulated genes were dependent on TRα, suggesting that TRα plays a dominant role early during T3induced intestinal remodeling 19 .…”
Section: Resultsmentioning
confidence: 95%
“…In addition to epithelial transformation, the connective tissue and muscles also remodel extensively, accompanied by shortening of the intestine 5,9 . More recently, we and others have used genome-editing tools such as TALEN and CRISPR/Cas enzymes 10 to study the role of endogenous TR genes during metamorphosis [11][12][13][14][15][16][17][18] . These studies revealed an important role of endogenous TRs during intestinal remodeling.…”
mentioning
confidence: 99%
“…5 ) that promote transcription of genes that drive metamorphosis ( Kulkarni and Buchholz, 2014 ; Sachs and Buchholz, 2019 ). For example, CS can induce expression of TRs to increase cellular sensitivity to the hormone signal ( Bonett et al, 2010 ; Kikuyama et al, 1993 ; Niki et al, 1981 ; Suzuki and Kikuyama, 1983 ), especially TR beta which is necessary for proper completion of metamorphosis ( Nakajima et al, 2019 ; Shibata et al, 2020a , 2020b ). The actions of CSs were synergistic with low or subthreshold doses of TH, producing strong induction of TR expression ( Bonett et al, 2010 ).…”
Section: Stress Hormones and Developmental Plasticitymentioning
confidence: 99%
“…Interestingly, we have shown previously that high levels of PRMT1 mRNA are expressed in an evolutionally conserved manner during the formation of the adult intestine in vertebrates, including intestinal maturation in mouse around 2–3 weeks after birth and intestinal remodeling during Xenopus laevis metamorphosis [ 31 ]. Importantly, intestinal remodeling during amphibian metamorphosis involves de novo development of adult stem cells in a T3-dependent process and that T3 signaling in the larval intestine is both necessary and sufficient for the formation of the adult stem cells through the dedifferentiation of some larval epithelial cells [ 32 40 ]. Furthermore, transgenic and knockdown studies in Xenopus have revealed a critical role of PRMT1 as a TR coactivator for amphibian metamorphosis and in the development of the adult stem cells [ 31 ].…”
Section: Introductionmentioning
confidence: 99%